Hadith #2 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
(the mother of the faithful believers) Al-Harith bin Hisham asked Allah’s Messenger (ﷺ) “O Allah’s Messenger (ﷺ)! How is the Divine Inspiration revealed to you?” Allah’s Messenger (ﷺ) replied, “Sometimes it is (revealed) like the ringing of a bell, this form of Inspiration is the hardest of all and then this state passes off after I have grasped what is inspired. Sometimes the Angel comes in the form of a man and talks to me and I grasp whatever he says.” ‘Aisha added: Veri
Grade: Sahih

Hadith #3 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The commencement of the Divine Inspiration to Allah’s Messenger (ﷺ) was in the form of good dreams which came true like bright daylight, and then the love of seclusion was bestowed upon him. He used to go in seclusion in the cave of Hira where he used to worship (Allah alone) continuously for many days before his desire to see his family. He used to take with him the journey food for the stay and then come back to (his wife) Khadija to take his food likewise again till suddenly the Truth des
Grade: Sahih

Hadith #20 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Whenever Allah’s Messenger (ﷺ) ordered the Muslims to do something, he used to order them deeds which were easy for them to do, (according to their strength and endurance). They said, “O Allah’s Messenger (ﷺ)! We are not like you. Allah has forgiven your past and future sins.” So Allah’s Apostle became angry and it was apparent on his face. He said, “I am the most Allah fearing, and know Allah better than all of you do.”
Grade: Sahih

Hadith #43 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Once the Prophet (ﷺ) came while a woman was sitting with me. He said, “Who is she?” I replied, “She is so and so,” and told him about her (excessive) praying. He said disapprovingly, “Do (good) deeds which is within your capacity (without being overtaxed) as Allah does not get tired (of giving rewards) but (surely) you will get tired and the best deed (act of Worship) in the sight of Allah is that which is done regularly.”
Grade: Sahih

Hadith #146 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The wives of the Prophet (ﷺ) used to go to Al-Manasi, a vast open place (near Baqi` at Medina) to answer the call of nature at night. `Umar used to say to the Prophet (ﷺ) “Let your wives be veiled,” but Allah’s Apostle did not do so. One night Sauda bint Zam`a the wife of the Prophet (ﷺ) went out at `Isha’ time and she was a tall lady. `Umar addressed her and said, “I have recognized you, O Sauda.” He said so, as he desired eagerly that the verses of Al-Hijab (the observing of
Grade: Sahih

Hadith #147 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) said to his wives, “You are allowed to go out to answer the call of nature. “
Grade: Sahih

Hadith #168 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) used to like to start from the right side on wearing shoes, combing his hair and cleaning or washing himself and on doing anything else.
Grade: Sahih

Hadith #198 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
When the ailment of the Prophet (ﷺ) became aggravated and his disease became severe, he asked his wives to permit him to be nursed (treated) in my house. So they gave him the permission. Then the Prophet came (to my house) with the support of two men, and his legs were dragging on the ground, between `Abbas, and another man.” ‘Ubaidullah (the sub narrator) said, “I informed `Abdullah bin `Abbas of what `Aisha said. Ibn `Abbas said: ‘Do you know who was the other man?’ I replied in th
Grade: Sahih

Hadith #212 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “If anyone of you feels drowsy while praying he should go to bed (sleep) till his slumber is over because in praying while drowsy one does not know whether one is asking for forgiveness or for a bad thing for oneself.”
Grade: Sahih

Hadith #222 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
(the mother of faithful believers) A child was brought to Allah’s Messenger (ﷺ) and it urinated on the garment of the Prophet. The Prophet (ﷺ) asked for water and poured it over the soiled place.
Grade: Sahih

Hadith #228 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Fatima bint Abi Hubaish came to the Prophet (ﷺ) and said, “O Allah’s Messenger (ﷺ) I get persistent bleeding from the uterus and do not become clean. Shall I give up my prayers?” Allah’s Messenger (ﷺ) replied, “No, because it is from a blood vessel and not the menses. So when your real menses begins give up your prayers and when it has finished wash off the blood (take a bath) and offer your prayers.” Hisham (the sub narrator) narrated that his father had also said, (the Prophe
Grade: Sahih

Hadith #229 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
I used to wash the traces of Janaba (semen) from the clothes of the Prophet (ﷺ) and he used to go for prayers while traces of water were still on it (water spots were still visible).
Grade: Sahih

Hadith #232 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
I used to wash the semen off the clothes of the Prophet (ﷺ) and even then I used to notice one or more spots on them.
Grade: Sahih

Hadith #242 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) said, “All drinks that produce intoxication are Haram (forbidden to drink).
Grade: Sahih

Hadith #248 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Whenever the Prophet (ﷺ) took a bath after Janaba he started by washing his hands and then performed ablution like that for the prayer. After that he would put his fingers in water and move the roots of his hair with them, and then pour three handfuls of water over his head and then pour water all over his body.
Grade: Sahih

Hadith #250 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) and I used to take a bath from a single pot called ‘Faraq’.
Grade: Sahih

Hadith #258 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Whenever the Prophet (ﷺ) took the bath of Janaba (sexual relation or wet dream) he asked for the Hilab or some other scent. He used to take it in his hand, rub it first over the right side of his head and then over the left and then rub the middle of his head with both hands.
Grade: Sahih

Hadith #261 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) and I used to take a bath from a single pot of water and our hands used to go in the pot after each other in turn.
Grade: Sahih

Hadith #262 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Whenever Allah’s Messenger (ﷺ) took a bath of Janaba, he washed his hands first.
Grade: Sahih

Hadith #263 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) and I used to take a bath from a single pot of water after Janaba.
Grade: Sahih

Hadith #271 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
It is as if I am just looking at the glitter of scent in the parting of the Prophet’s head hair while he was a Muhrim.
Grade: Sahih

Hadith #276 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Whenever any one of us was Junub, she poured water over her head thrice with both her hands and then rubbed the right side of her head with one hand and rubbed the left side of the head with the other hand.
Grade: Sahih

Hadith #287 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Whenever the Prophet (ﷺ) intended to sleep while he was Junub, he used to wash his private parts and perform ablution like that for the prayer.
Grade: Sahih

Hadith #294 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
While in menses, I used to comb the hair of Allah’s Messenger (ﷺ) .
Grade: Sahih

Hadith #296 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) used to lean on my lap and recite Qur’an while I was in menses.
Grade: Sahih

Hadith #298 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) and I used to take a bath from a single pot while we were Junub. During the menses, he used to order me to put on an Izar (dress worn below the waist) and used to fondle me. While in I`tikaf, he used to bring his head near me and I would wash it while I used to be in my periods (menses).
Grade: Sahih

Hadith #302 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
We set out with the Prophet (ﷺ) for Hajj and when we reached Sarif I got my menses. When the Prophet (ﷺ) came to me, I was weeping. He asked, “Why are you weeping?” I said, “I wish if I had not performed Hajj this year.” He asked, “May be that you got your menses?” I replied, “Yes.” He then said, “This is the thing which Allah has ordained for all the daughters of Adam. So do what all the pilgrims do except that you do not perform the Tawaf round the Ka`ba till you are clea
Grade: Sahih

Hadith #303 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Fatima bint Abi Hubaish said to Allah’s Messenger (ﷺ), “O Allah’s Messenger (ﷺ)! I do not become clean (from bleeding). Shall I give up my prayers?” Allah’s Messenger (ﷺ) replied: “No, because it is from a blood vessel and not the menses. So when the real menses begins give up your prayers and when it (the period) has finished wash the blood off your body (take a bath) and offer your prayers.”
Grade: Sahih

Hadith #305 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Whenever anyone of us got her menses, she, on becoming clean, used to take hold of the blood spot and rub the blood off her garment, and pour water over it and wash that portion thoroughly and sprinkle water over the rest of the garment. After that she would pray in (with) it.
Grade: Sahih

Hadith #306 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Once one of the wives of the Prophet (ﷺ) did I`tikaf along with him and she was getting bleeding in between her periods. She used to see the blood (from her private parts) and she would perhaps put a dish under her for the blood. (The sub-narrator `Ikrima added, `Aisha once saw the liquid of safflower and said, “It looks like what so and so used to have.”)
Grade: Sahih

Hadith #307 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
“One of the wives of Allah’s Messenger (ﷺ) joined him in I`tikaf and she noticed blood and yellowish discharge (from her private parts) and put a dish under her when she prayed.”
Grade: Sahih

Hadith #308 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
One of the mothers of the faithful believers (i.e. the wives of the Prophet (ﷺ) ) did I`tikaf while she was having bleeding in between her periods.
Grade: Sahih

Hadith #309 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
None of us had more than a single garment and we used to have our menses while wearing it. Whenever it got soiled with blood of menses we used to apply saliva to the blood spot and rub off the blood with our nails.
Grade: Sahih

Hadith #311 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
A woman asked the Prophet (ﷺ) about the bath which is taken after finishing from the menses. The Prophet (ﷺ) told her what to do and said, “Purify yourself with a piece of cloth scented with musk.” The woman asked, “How shall I purify myself with it” He said, “Subhan Allah! Purify yourself (with it).” I pulled her to myself and said, “Rub the place soiled with blood with it.”
Grade: Sahih

Hadith #312 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
An Ansari woman asked the Prophet (ﷺ) how to take a bath after finishing from the menses. He replied, “Take a piece a cloth perfumed with musk and clean the private parts with it thrice.” The Prophet (ﷺ) felt shy and turned his face. So I pulled her to me and told her what the Prophet (ﷺ) meant.
Grade: Sahih

Hadith #313 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
In the last Hajj of Allah’s Messenger (ﷺ) I assumed the Ihram for Hajj along with Allah Apostle. I was one of those who intended Tamattu` (to perform Hajj and `Umra) and did not take the Hadi (animal for sacrifice) with me. I got my menses and was not clean till the night of `Arafa I said, “O Allah’s Apostle! It is the night of the day of `Arafat and I intended to perform the Hajj Tamattu` with `Umra. Allah’s Messenger (ﷺ) told me to undo my hair and comb it and to postpone the `Umra
Grade: Sahih

Hadith #314 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
On the 1st of Dhul-Hijja we set out with the intention of performing Hajj. Allah’s Messenger (ﷺ) said, “Any one who likes to assume the Ihram for `Umra he can do so. Had I not brought the Hadi with me, I would have assumed the Ihram for `Umra. “Some of us assumed the Ihram for `Umra while the others assumed the Ihram for Hajj. I was one of those who assumed the Ihram for `Umra. I got menses and kept on menstruating until the day of `Arafat and complained of that to the Prophet. He told m
Grade: Sahih

Hadith #317 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Fatima bint Abi Hubaish used to have bleeding in between the periods, so she asked the Prophet (ﷺ) about it. He replied, “The bleeding is from a blood vessel and not the menses. So give up the prayers when the (real) menses begins and when it has finished, take a bath and start praying.”
Grade: Sahih

Hadith #322 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Fatima bint Abi Hubaish asked the Prophet, “I got persistent bleeding (in between the periods) and do not become clean. Shall I give up prayers?” He replied, “No, this is from a blood vessel. Give up the prayers only for the days on which you usually get the menses and then take a bath and offer your prayers.”
Grade: Sahih

Hadith #324 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
(the wife of the Prophet) Um Habiba got bleeding in between the periods for seven years. She asked Allah’s Messenger (ﷺ) about it. He ordered her to take a bath (after the termination of actual periods) and added that it was (from) a blood vessel. So she used to take a bath for every prayer.
Grade: Sahih

Hadith #325 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
(the wife of the Prophet) I told Allah’s Messenger (ﷺ) that Safiya bint Huyai had got her menses. He said, “She will probably delay us. Did she perform Tawaf (Al-Ifada) with you?” We replied, “Yes.” On that the Prophet (ﷺ) told her to depart.
Grade: Sahih

Hadith #327 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) said to me, “Give up the prayer when your menses begin and when it has finished, wash the blood off your body (take a bath) and start praying.”
Grade: Sahih

Hadith #330 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
(the wife of the Prophet) We set out with Allah’s Messenger (ﷺ) on one of his journeys till we reached Al- Baida’ or Dhatul-Jaish, a necklace of mine was broken (and lost). Allah’s Messenger (ﷺ) stayed there to search for it, and so did the people along with him. There was no water at that place, so the people went to Abu- Bakr As-Siddiq and said, “Don’t you see what `Aisha has done? She has made Allah’s Apostle and the people stay where there is no water and they have no water w
Grade: Sahih

Hadith #346 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
the mother of believers: Allah enjoined the prayer when He enjoined it, it was two rak`at only (in every prayer) both when in residence or on journey. Then the prayers offered on journey remained the same, but (the rak`at of) the prayers for non-travelers were increased.
Grade: Sahih

Hadith #368 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) used to offer the Fajr prayer and some believing women covered with their veiling sheets used to attend the Fajr prayer with him and then they would return to their homes unrecognized .
Grade: Sahih

Hadith #369 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
the Prophet (ﷺ) prayed in a Khamisa (a square garment) having marks. During the prayer, he looked at its marks. So when he finished the prayer he said, “Take this Khamisa of mine to Abu Jahm and get me his Inbijaniya (a woolen garment without marks) as it (the Khamisa) has diverted my attention from the prayer.” Narrated `Aisha: The Prophet (ﷺ) said, ‘I was looking at its (Khamisa’s) marks during the prayers and I was afraid that it may put me in trial (by taking away my attention).
Grade: Sahih

Hadith #376 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Anas bin Malik said, “My grandmother Mulaika invited Allah’s Messenger (ﷺ) for a meal which she herself had prepared. He ate from it and said, ‘Get up! I will lead you in the prayer.’ ” Anas added, “I took my Hasir, washed it with water as it had become dark because of long use and Allah’s Messenger (ﷺ) stood on it. The orphan (Damira or Ruh) and I aligned behind him and the old lady (Mulaika) stood behind us. Allah’s Messenger (ﷺ) led us in the prayer and offered two rak`a
Grade: Sahih

Hadith #379 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Allah Apostle prayed while I was lying like a dead body on his family bed between him and his Qibla.
Grade: Sahih

Hadith #403 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
(the mother of faithful believers) Allah’s Messenger (ﷺ) saw some nasal secretions, expectoration or sputum on the wall of the mosque in the direction of the Qibla and scraped it off.
Grade: Sahih

Hadith #420 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) used to start every thing from the right (for good things) whenever it was possible in all his affairs; for example: in washing, combing or wearing shoes.
Grade: Sahih

Hadith #421 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Um Habiba and Um Salama mentioned about a church they had seen in Ethiopia in which there were pictures. They told the Prophet (ﷺ) about it, on which he said, “If any religious man dies amongst those people they would build a place of worship at his grave and make these pictures in it. They will be the worst creature in the sight of Allah on the Day of Resurrection.”
Grade: Sahih

Hadith #428 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Um Salama told Allah’s Messenger (ﷺ) about a church which she had seen in Ethiopia and which was called Mariya. She told him about the pictures which she had seen in it. Allah’s Messenger (ﷺ) said, “If any righteous pious man dies amongst them, they would build a place of worship at his grave and make these pictures in it; they are the worst creatures in the sight of Allah.”
Grade: Sahih

Hadith #432 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
There was a black slave girl belonging to an ‘Arab tribe and they manumitted her but she remained with them. The slave girl said, “Once one of their girls (of that tribe) came out wearing a red leather scarf decorated with precious stones. It fell from her or she placed it somewhere. A kite passed by that place, saw it Lying there and mistaking it for a piece of meat, flew away with it. Those people searched for it but they did not find it. So they accused me of stealing it and started searc
Grade: Sahih

Hadith #447 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Once I saw Allah’s Messenger (ﷺ) at the door of my house while some Ethiopians were playing in the mosque (displaying their skill with spears). Allah’s Messenger (ﷺ) was screening me with his Rida’ so as to enable me to see their display. (`Urwa said that `Aisha said, “I saw the Prophet (ﷺ) and the Ethiopians were playing with their spears.”)
Grade: Sahih

Hadith #448 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Barirah came to seek my help regarding her manumission (freedom). I told herself you like I would pay your price to your masters but your Wala’ (allegiance) would be for me.” Her masters said, “If you like, you can pay what remains (of the price of her manumission), (Sufyan the sub-narrator once said), or if you like you can manumit her, but her (inheritance) Al-Wala would be for us. “When Allah’s Messenger (ﷺ) came, I spoke to him about it. He said, “Buy her and manumit her. No do
Grade: Sahih

Hadith #1125 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) offered the `Isha’ prayer (and then got up at the Tahajjud time) and offered eight rak`at and then offered two rak`at while sitting. He then offered two rak`at in between the Adhan and Iqama (of the Fajr prayer) and he never missed them.
Grade: Sahih

Hadith #1390 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) said, “If a woman gives in charity from her husband’s house …” (See next hadith)
Grade: Sahih

Hadith #1464 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) sent my brother, ‘Abdur Rahman with me to Tan’im for the ‘Umra, and he made me ride on the packsaddle (of a camel). ‘Umar said, “Be ready to travel for Hajj as it (Hajj) is one of the two kind of Jihad”.
Grade: Sahih

Hadith #2523 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
I went to `Aisha and she was wearing a coarse dress costing five Dirhams. `Aisha said, “Look up and see my slave-girl who refuses to wear it in the house though during the lifetime of Allah’s Messenger (ﷺ) I had a similar dress which no woman desiring to appear elegant (before her husband) failed to borrow from me.”
Grade: Sahih

Hadith #3198 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
I heard the Prophet (ﷺ), “Souls are like recruited troops: Those who are like qualities are inclined to each other, but those who have dissimilar qualities, differ.”
Grade: Sahih

Hadith #3512 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
— “Muhammad is no more than an Apostle and indeed many Apostles have passed away before him..” (3.144)
Grade: Sahih

Hadith #3662 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
Hind bint ‘Utba came and said, “O Allah’s Messenger! (Before I embraced Islam) there was no family on the surface of the earth I wished to see in degradation more than I did your family, but today there is no family on the surface of the earth I wish to see honored more than I did yours.” The Prophet (ﷺ) said, “I thought similarly, by Him in whose Hand my soul is!” She further said, “O Allah’s Messenger ! Abu Sufyan is a miser, so, is it sinful of me to feed my children from hi
Grade: Sahih

Hadith #4110 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
The Prophet (ﷺ) used to say in his bowings and prostrations, “Subhanaka Allahumma Rabbanã wa bihamdika, Allãhumma ighfirli” (Glorified be You, O Allah, our Lord! All the praises are for You. O Allah, forgive me)!”
Grade: Sahih

Hadith #4552 - Sahih al-Bukhari - Aisha bint Abi Bakr (Sahih al-Bukhari)
May Allah bestow His Mercy on the early emigrant women. When Allah revealed: “… and to draw their veils all over their Juyubihinna (i.e., their bodies, faces, necks and bosoms)…” (V.24:31) they tore their Murat (woolen dresses or waist-binding clothes or aprons etc.) and covered their heads and faces with those torn Muruts.
Grade: Sahih